2004
DOI: 10.1002/jsfa.1805
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of iron bioavailability from twenty elite late‐maturing tropical maize varieties using an in vitro digestion/Caco‐2 cell model

Abstract: An in vitro digestion/Caco-2 cell model was used to assess iron bioavailability of twenty elite latematuring tropical maize varieties grown in three diverse agroecologies in West and Central Africa (WCA). Kernel-iron concentration of the varieties, averaged across locations, varied from 19.2 to 24.4 mg kg −1 , while mean kernel-zinc concentration ranged between 19.4 and 24.6 mg kg −1 . Significant differences in iron bioavailability were observed among varieties, but the environment had no significant effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…growing environments had no effect on bioavailable Fe in maize (Oikeh et al 2004a); however, Pixley et al (2011a) detected larger E than GEI for Fe bioavailability in maize. It is therefore suggested that responses of cultivars to different production environments need to be well understood to improve the probability of predicting and identifying cultivars that are not only high in seed-Fe and/or -Zn concentrations but also these micronutrients are more bioavailable to absorption (Briat and Lobreaux 1997;Pixley et al 2011a).…”
Section: B Genotype â Environment Interaction and Relationships Betwmentioning
confidence: 92%
See 1 more Smart Citation
“…growing environments had no effect on bioavailable Fe in maize (Oikeh et al 2004a); however, Pixley et al (2011a) detected larger E than GEI for Fe bioavailability in maize. It is therefore suggested that responses of cultivars to different production environments need to be well understood to improve the probability of predicting and identifying cultivars that are not only high in seed-Fe and/or -Zn concentrations but also these micronutrients are more bioavailable to absorption (Briat and Lobreaux 1997;Pixley et al 2011a).…”
Section: B Genotype â Environment Interaction and Relationships Betwmentioning
confidence: 92%
“…For example, Oikeh et al (2003a) detected large variation in Fe bioavailability that ranged from 30% below to 88% above the reference control cultivar, TZB-SR. In some maize cultivars with high seed-Fe and -Zn concentrations (22-24 mg kg À1 ) the bioavailable Fe was 24%-36% higher than the reference control (Oikeh et al 2004a). Wheat Aegilops species and their derivatives are reported to possess high grain Fe and Zn concentrations (Chhuneja et al 2006;Neelam et al 2010a;Tiwari et al 2010).…”
Section: Mining Germplasm Collections For Natural Variation For Sementioning
confidence: 99%
“…Aluru et al (2011) and Drakakaki et al (2005) indicated that using a transgenic approach to introduce a soybean ferritin gene can increase both FECON and FEBIO, and they are correlated. However, by studying the crop varieties in the market, iron concentration was not significantly correlated with FEBIO (Glahn et al, 2002bOikeh et al, 2004;Vasconcelos et al, 2003;Welch et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it does not appear that screening crop varieties via phytate content will be useful, as both animal and Caco-2 models show no correlation with Fe availability among genotypes. 33,41,42,78 Although phytate is an inhibitor of Fe availability, these observations indicate that other factors in the seed appear to be responsible for the ultimate bioavailable levels of Fe and Zn. The most likely factors are polyphenolics and the nature of the complexes formed between Fe, Zn and this huge group of compounds.…”
Section: Justifi Cation For Use Of the In Vitro Digestion/caco-2 Cellmentioning
confidence: 85%
“…As a result, this model has been the most widely applied model for foods. It has found applications in development of infant foods; 39,40 in agriculture for screening plant cultivars for bioavailable iron; [41][42][43] in the pharmaceutical industry for developing improved iron supplements; 44 for studies of human milk and infant formula; [45][46][47][48] in fortifi ed ready-to-eat cereals; 49 in assessing elemental iron powders baked into breads; 50 in assessing the bioavailability of Fe from raisins and the effects of raisins on fortifi ed Fe in foods; 51,52 in food science for comparison of fortifi ed iron in milk and breads; 53,54 in assessing the effects of caseinates and casein phosphopeptides; 55,56 and in fundamental studies designed to investigate factors in digests of animal tissue (i.e. meat) that promote iron uptake.…”
Section: In Vitro Measurement Of Iron Bioavailabilitymentioning
confidence: 99%